An Anzalduan Reading of Ben Okri's In Arcadia (2002). Issue 3 (2nd July 2020) - Curr, Matthew
Summary: Set against Anzaldua's seminal text, Borderlands, this study of Okri's In Arcadia (2002) concerns itself with the author's psychological, emotional and artistic identity; torn as he is between African and European heritages, obliged to negotiate a middle ground or mestiza personality. What appears at first to be unqualified suffering, ignominy and stateless confusion for Lao/Okri, reveals itself in the course of the film crew's revelatory expedition to France, to be the existential groundwork for an identity that possesses insight, compassion and tolerance. More than that, the pain of existing in the shadow lands of English society stimulates Lao to develop the sensitive antennae of a true artist: he gains what Anzaldua defines as La Facultad, the ability to see below surface meanings and evince truths about cultures and those that inhabit their bounds. His nuanced mestiza character and artistic nature stand in stark contrast to the crass attitudes of entitlement and gauche lack of self-reflection evidenced by members of the film crew who all experience differing forms of grating confrontation and humiliation before they can reach a measure of that inner Arcadian peace, which most of them hardly realised they sought so earnestly.